Setting of import tolerance for quizalofop‐P‐ethyl in genetically modified maize. (20th April 2018) - ,; Brancato, Alba; Brocca, Daniela; Carrasco Cabrera, Luis; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Dow AgroSciences submitted a request to the competent national authority in Finland, to set an import tolerance for quizalofop‐P‐ethyl in grain from genetically modified maize containing aad‐1 gene. The data submitted in support of the request were found to be sufficient to derive a maximum residue level (MRL) proposal for quizalofop‐P‐ethyl maize grain. Adequate analytical methods for enforcement are available to control the residues of quizalofop‐P‐ethyl in maize grain. Based on the risk assessment results, EFSA concluded that the authorised use of quizalofop‐P‐ethyl on genetically modified maize containing aad‐1 gene and the subsequent import of maize grain in Europe will not result in a consumer exposure exceeding the toxicological reference value and therefore is unlikely to pose a risk to consumers' health.